2020
DOI: 10.1038/s41401-019-0336-3
|View full text |Cite
|
Sign up to set email alerts
|

Nimesulide increases the aldehyde oxidase activity of humans and rats

Abstract: An increasing number of drugs are metabolized by aldehyde oxidase (AOX), but AOX-mediated drug interactions are seldom reported due to the lack of appropriate inhibitors and inducers. A recent study reported that nimesulide (NIM) could increase the liver injury risk of methotrexate. The latter was mainly metabolized by AOX to form hepatotoxic 7-hydroxymethotrexate (7-OH MTX). Thus, we speculated that NIM could induce AOX. In this study, we investigated the potential induction of AOX activity by NIM using metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Maeda et al demonstrated regulation of the human AOX gene involving the Nrf2 pathway (Maeda et al 2012 ). In addition, Zhou et al reported increased AOX-mediated metabolism of methotrexate, increased AOX protein levels, and a minimal increase in AOX mRNA following treatment of human hepatocytes with the nonsteroidal anti-inflammatory drug nimesulide (Zhou et al 2020 ). Others have demonstrated induction of AOX activity, mRNA, and/or protein in animals by various compounds (e.g.…”
Section: Examples Of Metabolic Reactions Of Mao Substratesmentioning
confidence: 99%
“…Maeda et al demonstrated regulation of the human AOX gene involving the Nrf2 pathway (Maeda et al 2012 ). In addition, Zhou et al reported increased AOX-mediated metabolism of methotrexate, increased AOX protein levels, and a minimal increase in AOX mRNA following treatment of human hepatocytes with the nonsteroidal anti-inflammatory drug nimesulide (Zhou et al 2020 ). Others have demonstrated induction of AOX activity, mRNA, and/or protein in animals by various compounds (e.g.…”
Section: Examples Of Metabolic Reactions Of Mao Substratesmentioning
confidence: 99%